Peripheral Prosthetic Vascular Graft Infection: A 5-Year Retrospective Study - Giovanni De Caridi; Mafalda Massara; Chiara Barilla; Filippo Benedetto (Medical Sciences)
Background/Objectives: Peripheral prosthetic vascular graft infection represents a very serious complication after lower limb revascularization, with amputation and mortality rates up to 70% and 30%, respectively. This study was designed to determine the incidence of prosthetic graft infection, amputation, and mortality rate in our institution, analyzing different types of treatment. Methods: A retrospective cohort single institution review of peripheral prosthetic bypass grafts evaluated patient demographics, comorbidities, indications, location of bypass, type of prosthetic material, and case urgency and evaluated the incidence of graft infections, amputations, and mortality. Results: Between January 2016 and December 2021, a total of 516 bypasses were recorded (318 male, 198 female, mean age 74.2): 320 bypasses in venous material and 196 prosthetic bypasses using Dacron or PTFE. Among patients with a prosthetic bypass, 16 (8.2%) presented a graft infection at a mean follow-up of 39 months. Thirteen other patients who submitted to prosthetic peripheral bypass in other centers presented to our institution with a graft infection, so a total of 29 infected grafts were treated. Infected grafts were removed in 20 patients (68.9%), while a conservative treatment was helpful in nine cases (31.1%). The germs involved were Gram-negative in 27.6% and Gram-positive in 41.4%. During follow-up, we recorded five deaths (17.2%) and six amputations (20.7%) directly after bypass excision; another two amputations (6.9%) occurred after failure of the new bypass replacing the prosthesis removed. Conclusions: Redo-bypass, active infection at the time of bypass, and advanced gangrene were associated with a higher risk for prosthetic graft infection and major extremity amputation. Complete graft removal and replacement by venous material or Omniflow II represents the typical treatment. However, aggressive local treatment including drainage, debridement, vacuum-assisted closure therapy application, and muscle transposition seem to be a better solution in selected patients without the need for graft removal and with rates of limb salvage superior to those obtained with excisional therapy.